Nurse Nelly - Hossein, Rokeya Sakhawat; Quayum, Mohammad Abdul (Flinders University, Australia, 2012)
A translated short story from Bengali to English, authored by the acclaimed Bengali Muslim writer Rokeya Sakhawat Hossain.